Uji Penghambatan Aktivitas alfa-glukosidase Ekstrak dan Fraksi Daun Antidesma montanum Blume - Nofiantini, Nofiantini; Elya, Berna; Azizahwati, Azizahwati (Majalah Ilmu Kefarmasian, 2012)
alpha-Glucosidase inhibitor has known to be a therapeutic agent for diabetes mellitus (DM) treatment, especially type 2 DM. Based on previous studies. There are various plants that have the effect of inhibiting the activity of a-glucosidase, one of which is garu leaves (Antidesma montanum Blume). This research aimed to get the fraction which had the highest Il-glucosidase inhibiting activity from ethanol extract of garu leaves and identify the chemical compounds from the most active fraction. Simplisia powder was extracted by maseration using 80% ethanol then fractionated using n-hexane, ethyl acetate, and methanol. Inhibitory activity test was performed by measuring absorbance of p-nitrophenol, which produced by reaction between Il-glucosidase and p-nitrophenyl-u-l)-glucopyranoside, using microplate reader at 405 nm. The result showed that ethyl acetate fraction have the best Il-glucosidase inhibitory activity with IC50 values 138.38 ppm. The test of enzyme kinetics showed that ethyl acetate fraction inhibited competitively. The phytochemical screening showed that ethyl acetate fraction of garu leaves contained glycosides, tannins, and terpenes.